Relationship of Tuberculosis Radiographic Manifestation in Diabetic Patients with HbA1c Levels - Dana Jauhara Layali; Bintang YM Sinaga; Parluhutan Siagian; Putri Chairani Eyanoer (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: The relationship between diabetes mellitus (DM) and tuberculosis (TB) is a significant health problem and more prominent in developing countries where TB is endemic and DM prevalence increases. The prevalence of pulmonary TB increases with increasing prevalence of DM. Uncontrolled diabetic patients with high hemoglobin (HbA1c) levels cause TB to become more severe and are associated with higher mortality and also have a significant effect on radiological manifestations of pulmonary TB. Methods: The was a case-control study conducted between January to December 2016 at RSUP H Adam Malik, Medan to 43 with TB-DM patients and 41 TB-without DM patients was studied from. Radiological examination with chest radiograph was done in both groups of samples. The HbA1c levels was examined in the TB with DM group. Result: Compared with TB-without DM group, the TB with DM group significantly had far advanced tuberculosis lesions (OR=3.8; 95% CI=1.37-10.47; P=0.01), more atypical lesions atipikal (OR=6.29; 95% CI=2.43-16.25; P